Egypt's youth uprising : its global dimensions - Desker, Barry (2012)
Egypt’s current uprising is very much a rebellion of the youth. This sub-text cuts across a large swathe of North Africa and the Middle East, and to a certain extent, Asia as well. This global dimension of the youthful challenge will have far-reaching implications.